Audit Studies: Behind the Scenes With Theory, Method, and Nuance 2018
DOI: 10.1007/978-3-319-71153-9_1
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Audit Studies in the Social Sciences

Abstract: An audit study is a specific type of field experiment primarily used to test for discriminatory behavior when survey and interview questions induce social desirability bas. In this chapter, I first review the language and definitions related to audit studies and encourage adoption of a common language. I then discuss why researchers use the audit method as well as when researchers can and should use this method. Next, I give an overview of the history of audit studies, focusing on major developments and change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 258 publications
1
115
0
1
Order By: Relevance
“…Because audits are typically conducted in real‐world environments, they also tend to have greater external validity compared with lab‐based experiments. The basic audit design typically includes a field experiment in which an attribute is randomly assigned to one tester within a pair of similar or near‐identical testers to test the effect of that attribute on the outcome of interest (Gaddis, ).…”
Section: Audit Methods and Estimating Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because audits are typically conducted in real‐world environments, they also tend to have greater external validity compared with lab‐based experiments. The basic audit design typically includes a field experiment in which an attribute is randomly assigned to one tester within a pair of similar or near‐identical testers to test the effect of that attribute on the outcome of interest (Gaddis, ).…”
Section: Audit Methods and Estimating Discriminationmentioning
confidence: 99%
“…Each record and race contrast can be considered a separate experiment (Cox, ). We have a within or matched design on the criminal record signal and a between design on the race signal (Gaddis, ; Lahey & Beasley, ). Fear of arousing the suspicion of admissions officials or introducing potential bias led us to opt for a mixed within/between design across characteristics rather than for a full (four applications per institution) within design (Gaddis, ; Phillips, ; Weichselbaumer, , ).…”
Section: Design and Approachmentioning
confidence: 99%
“…gender and ethnicity). Different response rates (commonly referred to as "callback") provide causal evidence of discrimination (for overviews, see Gaddis 2018;Neumark 2016;Pager 2007). Across a wide range of countries, minority groups and labour-market segments, these studies have demonstrated that candidates with the same observable productivity-relevant characteristics are nonetheless treated differently, thus proving the existence of labourmarket discrimination beyond a reasonable doubt.…”
Section: Introductionmentioning
confidence: 99%
“…We test whether this difficult to observe behavior occurs by conducting an audit study. An audit study, also know as a correspondence study, is an experimental approach designed to identify hard-to-observe phenomena (Gaddis, 2017;Heckman, 1998). 5 The basic design of an audit study is uncomplicated and includes only a few steps.…”
Section: Methodsmentioning
confidence: 99%